The Relationship between Organisational Health and Teachers’ Absenteeism in Schools” A Case Study in a Private School in Amman, Jordan - Saleh, Mahasen (2019)
Educational systems have undergone unprecedented change all over the world. This is due to the continuous need for educational reform and the necessity to hold administrators accountable. This surge has created new challenges for principals, and it demands that schools consistently strive to meet the highest standards. Therefore, schools must maintain their organizational health to facilitate a productive work environment for teachers. The goal is to prevent teacher absenteeism since they are the main service providers. The objectives of an educational institution can only be achieved if their teachers are mentally and physically present. To date, there is no research focusing on a school’s organisational health (OH) and teacher absenteeism (TA). This study aims to explore the relationship between the level of OH and TA in a secondary private school in Amman, Jordan. The theoretical Framework was based on Nicholson’s “Attachment” Theory, Herzberg's Motivators Hygiene Factors, and Parsonian social systems theory. A quantitative analysis included a population consisting of 30 secondary school teachers. The organizational health inventory (OHI-S) of (Feldman & Hoy, 2000) was used to measure the health of the school. Questionnaires were provided to consider organizational factors of absenteeism and the attendance status of respondents. The data obtained was analysed using SPSS software version 21. A descriptive analysis utilizing the Pearson Correlation Coefficient determined the strength of the relationship between the two variables. The study revealed that there is a negative correlation between the school’s OH level and TA. From the perspective of the secondary teachers the resulting value was r= -0.581**. As such, to reduce teacher absenteeism, schools must maintain a good level of OH. In particular, the dimensions of Institutional Integrity, Resource Support and Consideration are essential. Furthermore, schools need to work on reducing workload, providing incentive programmes and having effective leadership that promotes teachers' engagement and welfare. Further research is highly recommended to investigate the relationship between these two variables. It would be beneficial to include public schools and the other levels of education for future studies. A comparative analysis between schools would also be useful focusing on OH and how it affects students’ academic achievement.